IMPLEMENTING SEMANTIC MAPPING STRATEGY TO ENHANCE STUDENTS’ ENGLISH VOCABULARY AND SPEAKING ACHIEVEMENTS - . Vedyanto; Y. Gatot Sutapa; Sudarsono . (Universitas Tanjungpura, 2016)
Abstract: This quasi experimental-based research evidently concentrated on the effectiveness of semantic mapping strategy in comparison to direct translation technique to enhance students’ English vocabulary and speaking achievements on descriptive texts. Students’ perception was additionally studied. The instruments were tests and questionnaires. One-way analysis of variance (ANOVA) was applied to analyse quantitative data obtained through the tests and an analytic scoring rubric was developed to support speaking performance assessment. The outcomes disclose that there is a significant dissimilarity observed through the individual total scores and F ratios obtained by the two groups. Semantic mapping affected the experimental students’ English vocabulary achievement powerfully and their English speaking achievement moderately. Moreover, their positive perception appeared. These indications, contrarily, did not apply to the control group treated with direct translation technique. To conclude, this strategy is superior to direct translation technique. Keywords: Semantic Mapping Strategy, English Vocabulary Achievement, English Speaking Achievement Abstrak: Penelitian quasi-eksperimental ini berfokus pada efektivitas strategi peta semantik sebagai perbandingan dari teknik terjemahan langsung dalam meningkatkan penguasaan kosakata dan kemampuan berbicara yang berhubungan dengan teks deskriptif. Persepsi siswa juga menjadi bahan penelitian. Instrumen yang digunakan meliputi tes dan kuesioner. Analisis variansi satu arah diterapkan untuk menganalisis data kuantitatif yang diperoleh melalui tes dan sebuah rubrik penilaian analitis dikembangkan untuk mendukung penilaian performa berbicara. Hasil penelitian memperlihatkan adanya perbedaan signifikan berdasarkan nilai individu secara keseluruhan dan rasio F yang diperoleh kedua kelompok. Strategi peta semantik membawa pengaruh kuat terhadap penguasaan kosakata dan pengaruh sedang terhadap kemampuan berbicara. Lebih lanjut, persepsi positif siswa muncul. Indikasi-indikasi ini sebaliknya tidak ditemukan pada kelompok kontrol yang belajar dengan menggunakan teknik terjemahan langsung. Alhasil, strategi peta semantik lebih unggul daripada teknik terjemahan langsung. Kata Kunci: Strategi Peta Semantik, Penguasaan Kosakata bahasa Inggris, Kemampuan Berbicara bahasa Inggris